Cluster Analysis Revealed Two Hidden Phenotypes of Cluster Headache - Yalinay Dikmen, Pinar; Ari, Cagla; Sahin, Erdi; Ertas, Mustafa; Mayda Domac, Fusun; Ilgaz Aydinlar, Elif; Sahin, Aysenur; Ozge, Aynur; Ozguner, Hilal; Karadas, Omer; Shafiyev, Javid; Vuralli, Doga; et al. (Frontiers in Neurology, 2022)
Objectives: Higher rates of cigarette smoking of patients with cluster headaches as well as in their parents have been reported. Personal cigarette smoking and secondhand tobacco exposure during childhood are both important factors leading to cluster headache onset and its clinical presentations. To create possible subgroups of patients with cluster headaches using cluster analysis. Our second goal was to investigate if cigarette smoking had any influence on the generation of subgroups of cluster headaches. Methods: A total of 209 individuals (mean (SD) age: 39.8 (11.3) years) participated in this cross-sectional study. All patients completed a semi-structured survey either face to face, preferably, or through phone interviews with a physician. The survey was composed of questions that addressed sociodemographic characteristics as well as detailed clinical features and treatment experiences. Results: Cluster analysis revealed two subgroups. Cluster 1 patients (n=81) had younger age at diagnosis (31.04 (9.68) vs. 35.05 (11.02) years; p=0.009), a higher number of autonomic symptoms (3.28 (1.16) vs. 1.99(0.95); p<0.001), and a better response to triptans (50.00% vs. 28.00; p<0.001) during attacks compared with the cluster 2 subgroup (n=122). Cluster 2 patients had higher rates of current smoking (76.0% vs. 33.0%; p=0.002), higher rates of smoking at diagnosis (78.0% vs. 32.0%; p=0.006), higher rates of parental smoking/tobacco exposure during childhood (72.0% vs. 33.0%; p=0.010), longer duration of attacks with (44.21 (34.44) min. vs. 34.51 (24.97) min; p=0.005) and without (97.50 (63.58) min. vs. (83.95 (49.07) min; p=0.035) treatment and higher rates of emergency department visits in the last year (81.0% vs. 26.0%; p<0.001). Conclusions: Cluster 1 and cluster 2 patients had different phenotypic features, possibly indicating differing underlying mechanisms. The cluster 1 phenotype may suggest a genetic or biology-based etiology. The cluster 2 phenotype seems to have a more severe form of the disease, possibly related to epigenetic mechanisms. Toxic exposure to cigarettes, either personally or secondarily, was the most prominent factor in the cluster 2 subgroup. We need more studies to elaborate on the missing links of neurobiologic pathways of cigarette smoking regarding the identified distinct phenotypic classes of patients with cluster headaches.